Remote Control and Monitoring Via Internet on Distributed Data Acquisition - Mohd Hanapi, Zurina (2004)
The concept of remote control and monitoring becomes an essential feature in many systems nowadays. Remote control allows clients to control their homes from any places, whereas remote monitoring provides the clients the ability to monitor their home or premises when they are away. The key advantage of this application is client has the ability to control and monitor their home remotely for security and safety reasons. From the analysis have been made, in Malaysia, Internet subscribers are growing rapidly from one year to another. The demand of having remote technology using Internet has made this area favourable, thus, it is chosen to be studied and discussed extensively in this thesis. A method of developing a remote control and monitoring system based on distributed data acquisition using the Internet is established. This system is based on client/server system in which the host computer where the program is installed, is set as a server where static IP address is assigned. For the purpose of control and monitoring tasks, the main program that consists the status of appliances is displayed. It is a user friendly system with good graphical user interface (GUI). The program is developed using the features in LabVIEW version 6i and its Internet Developer Toolkit. The I/O modules attached to the appliances are connected directly to the server via serial port. These I/O modules are based on the concept of data acquisition system (DAQ). The appliances can be controlled from the client PC by browsing the server website. Some necessary data are required to be sent to the server. Once the server is running, monitoring capability is enabled. Generally, this system is part of smart technology that has been developed to increase our quality of life, provide convenience environment and also act as an active partner in managing our busy life. It is a very user-friendly system with good GUI that gives a client an easy working environment. In a nutshell, this system gives a better security for the homes owner by giving them an authority to control and monitor their house from anywhere.